HUBUNGAN PENGETAHUAN TENTANG DIET DIABETES MELLITUS DENGAN PERILAKU DIET PENDERITA DIABETES MELLITUS - Ridwan, Achmad; Putro, Heri Pramono (Akademi Keperawatan Pamenang, 2012)
The Increasing of Diabetes Mellitus prevalence in several developing countries, for the impact of wealthy in those countries, has been recently much watched. The increasing salary and the change of life style especially in big cities causes the increasing of degenerative disease. Prevalence such as Diabetes Mellitus (DM). The type 2 of Diabetes Mellitus tends to occur to individualist with obesity. Obesity is the main trigger for the type 2 Diabetes Mellitus for that diet program is the main order action to do. The purpose of this is to identify the knowledge relation of DM diet with DM sufferers diet behaviour.The observation design used is analytic withÂ cross sectional. With Fiety Population and forty-four respondents as the samples who have inclusive and exclusive criteria. The taking of the samples is using simple random sampling technique. Methods of data collection in this study using a questionnaire, then the data were analyzed by stage editing, coding, scoring, tabulating. Analysis date be used Spearmen Correlation From the result of observation it can be gained that most of respondents have good knowledge, 12 respondents (27,3%) and the good DM diet behaviour is 16 respondents (36,4%). From the result spearmen correlation, itâs gained significant number 0,000 < 0,005 that means Ho rejected. It means that the knowledge relation about diet DM with DM suffers diet behaviour with very strong category.The knowledge of respondents about DM diet, increase the knowledge, information, and also joins in the health counselling especially about DM diet in order toÂ get maximal diet behaviour, so complication will not occur and the suffer can live happily.Â